The Iron-chelator, N,N'-bis (2-hydroxybenzyl) Ethylenediamine-N,N'-diacetic acid is an Effective Colistin Adjunct against Clinical Strains of Biofilm-Dwelling Pseudomonas aeruginosa - Karla Mettrick; Karl Hassan; Iain Lamont; David Reid (MDPI AG, 2020)
Targeting the iron requirement of Pseudomonas aeruginosa may be an effective adjunctive for conventional antibiotic treatment against biofilm-dwelling P. aeruginosa. We, therefore, assessed the anti-biofilm activity of N,N'-bis (2-hydroxybenzyl) ethylenediamine-N,N'-diacetic acid (HBED), which is a synthetic hexadentate iron chelator. The effect of HBED was studied using short-term (microtitre plate) and longer-term (flow-cell) biofilm models, under aerobic, anaerobic, and microaerobic (flow-cell) conditions and in combination with the polymyxin antibiotic colistimethate sodium (colistin). HBED was assessed against strains of P. aeruginosa from patients with cystic fibrosis and the reference strain PAO1. HBED inhibited growth and biofilm formation of all clinical strains under aerobic and anaerobic conditions, but inhibitory effects against PAO1 were predominantly exerted under anaerobic conditions. PA605, which is a clinical strain with a robust biofilm-forming phenotype, was selected for flow-cell studies. HBED significantly reduced biomass and surface coverage of PA605, and, combined with colistin, HBED significantly enhanced the microcolony killing effects of colistin to result in almost complete removal of the biofilm. HBED combined with colistin is highly effective in vitro against biofilms formed by clinical strains of P. aeruginosa.